2002
DOI: 10.1111/j.1755-6686.2002.tb00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Home training experience in peritoneal dialysis patients

Abstract: The objective of nursing is to increase health and well being, prevent morbidity and obtain the best physical and social rehabilitation. The nurse's role in Peritoneal Dialysis (PD) consists of promoting and supporting patients to perform self-care. In the'Text Book of Peritoneal Dialysis, published in 2000,the chapter dedicated to the nurses' role says:"Regular home visits are an important part of follow-up care, as the family and patient need to realize that continuing support is available... It is advisable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…Increased distance could lead to deficiencies in PD training, dietary education, and response time for complications. Home visits and PD training reinforcement, which have reduced peritonitis episodes in several observational studies (20,21), are difficult to provide for patients living farther away. In addition, local healthcare factors could greatly affect micropolitan and rural PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased distance could lead to deficiencies in PD training, dietary education, and response time for complications. Home visits and PD training reinforcement, which have reduced peritonitis episodes in several observational studies (20,21), are difficult to provide for patients living farther away. In addition, local healthcare factors could greatly affect micropolitan and rural PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Training at home has been considered to offer many benefits, such as higher patient satisfaction and acceptance, improved home assessment, individualized education, effective interaction and active family involvement [51]. The study reported by Castro et al [39] (Table 2) showed that peritonitis rates decreased from 1 episode per 24.5 patient-months (0.49 episodes per patient-year) to 1 episode per 44.4 patient-months (0.27 episodes per patient-year) after application of homebased training for 84 new PD patients. Unfortunately, no Pvalue of the comparison was reported and the study may have been potentially confounded by co-intervention bias.…”
Section: Home Trainingmentioning
confidence: 99%
“…comfortable chairs) not as a hospital. One study has shown improved outcomes for patients taught in their home compared with training at the hospital (Castro et al 2002). For older patients especially, training and visits at home would make them feel more comfortable partly because there is no need for transportation to the hospital (Riemann 2011).…”
Section: Training Environmentmentioning
confidence: 99%